2007
DOI: 10.3892/ijmm.20.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset olfactory deficits and mitral cell loss in mice lacking prion protein with ectopic expression of Doppel

Abstract: Abstract. Several lines of prion protein gene (Prnp)-knockout mice such as ZrchI, ZrchII, Npu, Ngsk and Rcm0 have been generated. Of these, ZrchII, Ngsk and Rcm0 exhibit late-onset ataxia due to ectopic expression of Doppel (Dpl); a result of damage to the splicing acceptor of Prnp exon 3. Recently, we developed another line of Prnp -/-mice (Rikn), which was generated by gene targeting with more nucleotides by replacing intron 2 with the pgk-neo gene (cf. Ngsk Prnp -/-mice) and showed not only ataxia but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…In our previous study, Prnp −/− mice aged over 60 weeks showed not only ataxia but also poorer olfactory sensitivity than the other Prnp −/− mouse line ZrchI assessed (Fig. ) . Histopathologically, elderly Rikn Prnp −/− mice show mitral cell loss and concomitant gliosis of astrocytes.…”
Section: Altered Physiologic Functionmentioning
confidence: 73%
“…In our previous study, Prnp −/− mice aged over 60 weeks showed not only ataxia but also poorer olfactory sensitivity than the other Prnp −/− mouse line ZrchI assessed (Fig. ) . Histopathologically, elderly Rikn Prnp −/− mice show mitral cell loss and concomitant gliosis of astrocytes.…”
Section: Altered Physiologic Functionmentioning
confidence: 73%
“…Some lines of Prnp / mice (ZrchII, Ngsk, Rcm0, and Rikn) expressing the PrP-like protein Doppel (Dpl) [36], which is encoded by Prnd, exhibit a late-onset ataxia. Our line of Prnp -/-mice (Rikn) showed not only ataxia but also lower olfactory sensitivity than the other Prnp -/-mouse line ZrchI at over 60 weeks of age [46]. Furthermore, Rikn Prnp -/-splenocytes elicited lower cell proliferation rates than Prnp +/+ or Zrch I Prnp -/-splenocytes after lipopolysaccharide (LPS) stimulation and showed sporadic nerve cells in the cerebral cortex and deeper structure [47].…”
Section: Prp C Expression and Phagocytotic Abilitymentioning
confidence: 95%
“…Mitral cells send rows of axons to internal granular layer (IGl), and then transfer information to a number of areas in the brain, including the PC, EC and amygdala . It has been demonstrated that the number of mitral cells tended to reduce in the aged rodent OB, resulting in olfactory deficits . Therefore, the degeneration of mitral cells in APP/PS1 mice is also one of the factors that led to olfactory deficits.…”
Section: Discussionmentioning
confidence: 69%
“…29 It has been demonstrated that the number of mitral cells tended to reduce in the aged rodent OB, resulting in olfactory deficits. [30][31][32] Therefore, the degeneration of mitral cells in APP/PS1 mice is also one of the factors that led to olfactory deficits.…”
Section: Discussionmentioning
confidence: 99%